Cassava-maize intercropping systems in southern Nigeria: radiation use efficiency, soil moisture dynamics, and yields of component crops - Nwokoro, C.C.; Kreye, C.; Necpalova, M.; Adeyemi, O.; Barthel, M.; Pypers, P.; Hauser, S.; Six, Johan (Elsevier, 2022)
Efficient utilization of incident solar radiation and rainwater conservation in rain-fed smallholder cropping systems require the development and adoption of cropping systems with high resource use efficiency. Due to the popularity of cassava-maize intercropping and the food security and economic importance of both crops in Nigeria, we investigated options to improve interception of photosynthetically active radiation (IPAR), radiation use efficiency (RUE), soil moisture retention, and yields of cassava and maize in cassava-maize intercropping systems in 8 on-farm researcher-managed multi-location trials between 2017 and 2019 in different agro-ecologies of southern Nigeria. Treatments were a combination of (1) maize planting density (low density at 20,000 maize plants ha-1 versus high density at 40,000 maize plants ha-1, intercropped with 12,500 cassava plants ha-1); (2) fertilizer application and management targeting either the maize crop (90 kg N, 20 kg P and 37 kg K ha-1) or the cassava crop (75 kg N, 20 kg P and 90 kg K ha-1), compared with control without fertilizer application. Cassava and maize development parameters were highest in the maize fertilizer regime, resulting in the highest IPAR at high maize density. The combined intercrop biomass yield was highest at high maize density in the maize fertilizer regime. Without fertilizer application, RUE was highest at low maize density. However, the application of the maize fertilizer regime at high maize density resulted in the highest RUE, soil moisture content, and maize grain yield. Cassava storage root yield was higher in the cassava fertilizer regime than in the maize fertilizer regime. We conclude that improved IPAR, RUE, soil moisture retention, and grain yield on nutrient-limited soils of southern Nigeria, or in similar environments, can be achieved by intercropping 40,000 maize plants ha-1 with 12,500 cassava plants ha-1 and managing the system with the maize fertilizer regime. However, for higher cassava storage root yield, the system should be managed with the cassava fertilizer regime.